Voyages to the planets - Fraknoi, Andrew; Morrison, David 1940-; Wolff, Sidney C. (Brooks/Cole--Thomson Learning, 2004)
VOYAGES TO THE PLANETS provides students and professors with the ideal combination of authors and experience. It is written by an award-winning astronomy educator (Fraknoi) and two distinguished research scientists (Morrison at NASA and Wolff at NOAO). This author team combines the latest science with classroom-tested teaching strategies and a student-friendly approach. Through unique group activities and a focus on astronomy as a human endeavor, the authors engage and involve students, helping them both understand and enjoy astronomy. The market-leading technology package includes access to InfoTrac(r) College Edition (free!) and TheSky Student Edition CD-ROM (free!), as well as an optional package with the RedShift College Edition CD-ROM (including animations) along with an accompanying workbook.